The impact of social media (YouTube) towards the behavioral change of Generation Z - Hang, Wan Shin; Foo, Lisa Chin Yee; Kang, Michelle Wen Theng; Wong, Sher-Yen (2018)
In today's world, social media has become a vital part among new generations of digital natives. Past researches have proven that majority of teenagers in Generation Z is more or less affected by their addiction or daily usage of social media platforms. In expansion of the researches, this research paper aims to find out whether Generation Z, aged between 6 to 23 years old are different in behavior because of their experiences in YouTube. Specifically, our research explores the factors of YouTube as a social platform affect the behavior of Generation Z in terms of their attitude, personalities, mentality, lifestyle, values and belief. Likewise, our research paper uses Social Cognitive theory developed by Albert Bandura to explain the phenomena of the impact of YouTube towards behavioral change in Generation Z. Few research objectives were also developed in this research paper to find out whether our target respondents is dedicated in the usage of YouTube, the factors of YouTube that they are attracted to and the behavior effect that they experienced from the social platform. Thus, this research is carried out to investigate the impact of social media (YouTube) towards the behavioural change of Generation Z in Subang Jaya. The independent variables which affect the behavioural change of Generation Z are YouTube content and YouTubers’ influences. This research aim is to investigate the relationship between the independent variables and dependent variable. A total of 262 sets of questionnaire had been distributed to the Form 4 students in 9 secondary schools of Subang Jaya to obtain the data. Reliability Test, Pearson’s Correlation Analysis, Independent Sample t-Test had been used to analyse the result. The major findings of this research are YouTubers’ influences have significant relationship with the behavioural change of Generation Z and there is also a significant difference between YouTube influences and respondents’ gender. However, there is no significant relationship between YouTube content and behavioural change of Generation Z and respondents’ gender also has no significant difference with YouTube content. Managerial implication, limitations of this research and recommendations for future research have been provided.